Correlation between Multidrug-Resistant Bacteria Colonization and Bloodstream Infections in Children with Hematolymphoid Malignancies at a Tertiary Cancer Center in India - Salifu, Nihad; Narula, Gaurav; Prasad, Maya; Biswas, Sanjay; Kelkar, Rohini; Banavali, Shripad (Indian Journal of Medical and Paediatric Oncology, 2021)
Background Bloodstream infections with drug-resistant bacteria are associated with a higher morbidity and mortality. Based on previous studies in our institution demonstrating a rising incidence of multidrug resistant organism (MDR) bacteria in bloodstream infections (BSI) and high prevalence of enteric colonization with MDR, the “de-escalation” strategy for empirical antibiotics was adopted in the management of febrile neutropenia in children with hematolymphoid malignancies and MDR colonization. An audit was carried out to determine whether surveillance rectal swabs correlated with blood cultures in febrile neutropenia.Methods Patient data from January 2015 to July 2016 was examined. Rectal swabs of children with hematolymphoid malignancies were obtained at presentation. Blood cultures were taken during febrile neutropenia. Data were analyzed using SPSS version 24.0. The significance level was set at p < 0.05.Results Most patients (62.1%) with confirmed BSI were colonized with either extended-spectrum β-lactamase producing organisms (ESBLO) (31.9%) or MDR (30.2%). Majority 116 (62.7%) developed BSI caused by either MDR or ESBLO. In contrast, only 12 (10.6%) patients colonized by sensitive bacteria, developed BSI caused by either MDR or ESBLO. These differences were statistically significant (p < 0.001). Thus, the baseline rectal swab had a sensitivity and a specificity of 90.6% and 59.4%, respectively, in predicting BSI with either MDR or ESBLO.Conclusions We conclude that high prevalence of MDR colonization at presentation significantly results in MDR BSI, which further results in a significant increase in intensive care unit admissions and mortality. This would justify the use of a “de-escalation” antibiotic policy. Whether such a strategy has been successful in impacting outcomes, would need further study.
Keywords: Bloodstream; colonization; enteric; infections